2008
DOI: 10.5194/angeo-26-1173-2008
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic and ionospheric data analysis over Antarctica: a contribution to the long term trends investigation

Abstract: Abstract. The analysis of the f oF 2 ionosonde data acquired at mid and high latitudes reveals a general decreasing of the F2 plasma frequency over more than two solar cycles, showing steeper trends over the high latitude stations and, in particular, over Antarctica. A careful analysis of the f oF 2 hourly data, opportunely catalogued in different levels of magneto-ionospheric conditions, highlights the role of the geomagnetic activity in the secular change of the ionosphere and confirms the latitudinal depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Information Content applied to foF2 monthly medians from a set of stations at high southern latitudes in dependence on time. The time scale Τκ of about 500 years is comparable with that obtained for the geomagnetic secular variation over Antarctica (Alfonsi et al, 2008).…”
Section: Long-term Trends In Differentsupporting
confidence: 79%
See 1 more Smart Citation
“…Information Content applied to foF2 monthly medians from a set of stations at high southern latitudes in dependence on time. The time scale Τκ of about 500 years is comparable with that obtained for the geomagnetic secular variation over Antarctica (Alfonsi et al, 2008).…”
Section: Long-term Trends In Differentsupporting
confidence: 79%
“…As the geomagnetic activity may influence ionospheric trends a new approach has been developed by De Franceschi et al (1999) and Alfonsi et al (2002Alfonsi et al ( , 2008) using a special magnetic activity catalogue for ionospheric applications (MACap). With this catalogue foF2 data have been isolated for quiet geomagnetic conditions.…”
Section: Long-term Trends In Differentmentioning
confidence: 99%
“…Alfonsi et al (2002Alfonsi et al ( , 2008 used a special magnetic activity catalogue for ionospheric applications (MACap). With this catalogue foF2 data have been isolated for quiet geomagnetic conditions.…”
Section: F2 Region Of the Ionospherementioning
confidence: 99%
“…[ 16 ] stressed the need for long-term climatological observations of solar-terrestrial phenomena to benefit the science and applications. [ 17 ] highlighted the role of the geomagnetic activity in the secular change of the ionosphere and confirms the latitudinal dependence of the trends. [ 18 ] tracked a complete night-time Weddell Sea Anomaly (WSA) - the WSA in the ionosphere is characterized by higher plasma densities at night than during the day in the region near the Weddell Sea - and strong horizontal plasma flows that registered the high-conductivity regions of the South Atlantic Magnetic Anomaly (SAMA), and revealed that the strong east-west hemispherical difference was due to the SAMA.…”
Section: Remote Sensors At the Sasmentioning
confidence: 74%
“…This type of sensor would provide information about the wave front distortion of a GNSS signal caused by electron density irregularities, which giving rise to highly transient and a random amplitude and phase modulation of the GNSS signal. Such systems have been adopted by several groups for both scientific purposes and space weather applications (e.g., [ 17 , 25 ]).…”
Section: Remote Sensors At the Sasmentioning
confidence: 99%